2016
DOI: 10.3389/fpls.2016.00849
|View full text |Cite|
|
Sign up to set email alerts
|

Reference Genes for qPCR Analysis in Resin-Tapped Adult Slash Pine As a Tool to Address the Molecular Basis of Commercial Resinosis

Abstract: Pine oleoresin is a major source of terpenes, consisting of turpentine (mono- and sesquiterpenes) and rosin (diterpenes) fractions. Higher oleoresin yields are of economic interest, since oleoresin derivatives make up a valuable source of materials for chemical industries. Oleoresin can be extracted from living trees, often by the bark streak method, in which bark removal is done periodically, followed by application of stimulant paste containing sulfuric acid and other chemicals on the freshly wounded exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…However, when different tissues and total samples were considered, all V n /V n + 1 values were still above 0.15 ( Figures 5C,D ), and thus the cut-off value of 0.15 was somewhat strict in these cases. Many studies have shown that the use of 0.15 as a cut-off value is just a recommendation, and whether 0.15 is actually used is dependent on the data ( Silveira et al, 2009 ; Fernandez et al, 2011 ; Lu et al, 2013 ; De Lima et al, 2016 ). Generally, a reliable result could be obtained by using three reference genes in the majority of experiments ( Toegel et al, 2007 ; Maroufi et al, 2010 ; Wang et al, 2014 ; Wang and Lu, 2015 ; Li M.Y.…”
Section: Resultsmentioning
confidence: 99%
“…However, when different tissues and total samples were considered, all V n /V n + 1 values were still above 0.15 ( Figures 5C,D ), and thus the cut-off value of 0.15 was somewhat strict in these cases. Many studies have shown that the use of 0.15 as a cut-off value is just a recommendation, and whether 0.15 is actually used is dependent on the data ( Silveira et al, 2009 ; Fernandez et al, 2011 ; Lu et al, 2013 ; De Lima et al, 2016 ). Generally, a reliable result could be obtained by using three reference genes in the majority of experiments ( Toegel et al, 2007 ; Maroufi et al, 2010 ; Wang et al, 2014 ; Wang and Lu, 2015 ; Li M.Y.…”
Section: Resultsmentioning
confidence: 99%
“…The cDNA was amplified according to the Takara rr820a kit (Takara, Shiga, Japan), and the expression levels of the genes were calculated using the 2 -ΔΔCt method [39]. The UBI [40] gene was used to normalize the transcript profiles. ).…”
Section: Qrt-pcr Analysismentioning
confidence: 99%
“…Hence, the threshold of 0.15 was slightly rigorous in these experimental conditions. Numerous studies have indicated that the application of a threshold of 0.15 is merely a suggestion, and whether it is practically applied is determined by the data [52][53][54].…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Auth...mentioning
confidence: 99%